REPRESENTASI PEREMPUAN PENYINTAS KEKERASAN SEKSUAL DALAM FILM LIKE & SHARE (2022) - Maharani, Mandu; Sunarto, Sunarto; Hasfi, Nurul (Interaksi Online, 2024)
Women with experiences of sexual violence are often viewed as individuals who cannot rise and live their lives as they did before. This perception stems from a patriarchal ideology that oppresses women through sexual violence, causing women who have experienced such actions to be seen as degraded, inferior, and impure. However, Gina S. Noer, as the writer and director, along with Chand Parwez Servia, the producer of the film Like & Share (2022), strive to show how women can break free from these oppressive thoughts by portraying female survivors of sexual violence who are able to recover and find meaning in their traumatic experiences. The research titled ‘The Representation of Female Survivors of Sexual Violence in the Film Like & Share (2022)’ aims to describe female survivors and the actualization of Gina and Chand's statements regarding the film through the lens of critical theory: gender and race in organizational communication and the muted group theory. The research employs a qualitative descriptive method with a critical paradigm and Schleiermacher's hermeneutic analysis approach. The research results show that the character Sarah experiences rape and Online Gender-Based Violence (OGBV), while Fita faces OGBV. Both have gone through various stages, ultimately reaching the stage of acceptance as female survivors of sexual violence. Character analysis reveals that Sarah goes through stages of denial, depression, problem-solving, and acceptance, while Fita goes through stages of anger, problem-solving, and acceptance. Furthermore, the hermeneutics of the message conveyed by Gina and Chand regarding female survivors of sexual violence in the film Like & Share is also successfully actualized through scenes in the film that depict female as survivors of sexual violence who are able to heal and accept themselves despite having to overcome various obstacles in society.